2017
DOI: 10.3389/fpsyg.2017.00354
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Autonomous and Controlled Motivation in Exercise Intentions of Participants in a Mass Cycling Event

Abstract: Purpose: This study used self-determination theory to examine the role of participants' autonomous and controlled motivation to exercise and to participate in a challenging mass cycling event and investigated whether the event enhanced intended and actual exercise behavior among the participants.Method: Two hundred and twenty-eight subjects, having participated in the cycling event, completed a questionnaire shortly after the event and again 4 months later. The questionnaire measured self-reported cycling and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 50 publications
2
12
0
1
Order By: Relevance
“…Indeed, the present study found that valued exercise-related outcomes were drivers for continued exercise participation amongst participants who appeared to be more regularly physically active. Consistent with SDT and previous research, more autonomous motivation rather than controlled or externally driven motivation are associated with regular exercise behaviour (22,23) . The strongest predictor of exercise maintenance is personally valued outcomes (23) .…”
Section: Discussionsupporting
confidence: 88%
“…Indeed, the present study found that valued exercise-related outcomes were drivers for continued exercise participation amongst participants who appeared to be more regularly physically active. Consistent with SDT and previous research, more autonomous motivation rather than controlled or externally driven motivation are associated with regular exercise behaviour (22,23) . The strongest predictor of exercise maintenance is personally valued outcomes (23) .…”
Section: Discussionsupporting
confidence: 88%
“…This study has some limitations, since the cross-sectional research did not allow causal inferences to be made among the variables studied. To conclude, in future research, gathering the data at two different times would provide a wider dataset and enhanced knowledge [53] about whether the years of experience of athletes are related to, or the extent to which they are may be related to, their participation motivations. Another interesting research line would be to analyse the differences between marathoners' male and female experiences, since previous research [18,19] has shown significant differences in relation to the motivational variables according to gender.…”
Section: Discussionmentioning
confidence: 99%
“…The cross-sectional design of the research was a limitation, since it did not allow causal inferences between the studied variables. In the future, collecting the data in two different moments would help to improve the knowledge about athletes' motives of participation in mass sports events [73]. Also, it would be worth examining the motivations for participating in mass sporting events in other sports, as this would allow comparative analyses to be carried out in the future.…”
Section: Final Conclusionmentioning
confidence: 99%